Genetic Basis for Congenital Heart Disease: Revisited. Issue 21 (20th November 2018) - Pierpont, Mary Ella; Brueckner, Martina; Chung, Wendy K.; Garg, Vidu; Lacro, Ronald V.; McGuire, Amy L.; Mital, Seema; Priest, James R.; Pu, William T.; Roberts, Amy; Ware, Stephanie M.; Gelb, Bruce D.; et al.
Abstract : This review provides an updated summary of the state of our knowledge of the genetic contributions to the pathogenesis of congenital heart disease. Since 2007, when the initial American Heart Association scientific statement on the genetic basis of congenital heart disease was published, new genomic techniques have become widely available that have dramatically changed our understanding of the causes of congenital heart disease and, clinically, have allowed more accurate definition of the pathogeneses of congenital heart disease in patients of all ages and even prenatally. Information is presented on new molecular testing techniques and their application to congenital heart disease, both isolated and associated with other congenital anomalies or syndromes. Recent advances in the understanding of copy number variants, syndromes, RASopathies, and heterotaxy/ciliopathies are provided. Insights into new research with congenital heart disease models, including genetically manipulated animals such as mice, chicks, and zebrafish, as well as human induced pluripotent stem cell–based approaches are provided to allow an understanding of how future research breakthroughs for congenital heart disease are likely to happen. It is anticipated that this review will provide a large range of health care–related personnel, including pediatric cardiologists, pediatricians, adult cardiologists, thoracic surgeons, obstetricians, geneticists, genetic counselors, and other related clinicians, timely information on the genetic aspects of congenital heart disease. The objective is to provide a comprehensive basis for interdisciplinary care for those with congenital heart disease.